Sequencing the Southern Iberian Late Neolithic hypogeum cemetery of La Beleña through radiocarbon dating and Bayesian modeling. - Santana-Cabrera, Jonathan; Caro-Herrero, José Luis; Camalich-Massieu, Maria Dolores; Aranda-Jimenez, Gonzalo; Martin-Socas, Dimas (Cambridge University Press, 2024)
This study aims to determine the chronological sequence of the collective burials in the hypogea of the prehistoric cemetery ofLa Bele˜na (Cabra, C´ordoba) through Bayesian analyses of 14C dates obtained from human remains. The data from this site are not only key to grasping the phenomenon of the introduction and spread of hypogea throughout the western Mediterranean, but to gain insight into multi-stage funerary practices during the Late Neolithic/Chalcolithic. The dataset comprises 14C dates of 71 of the 79 individuals placed in five of La Bele˜na’s six hypogea. The findings suggest: (i) La Bele˜na is one of the oldest assemblages of hypogea in Iberia, (ii) that this type of collective burial spread rapidly throughout the western Mediterranean area, (iii) that La Bele˜na is marked by two main phases of funerary activity interspersed by brief burial surges, (iv) funerary intensity at La Bele˜na increased between cal BC 3400–2900 (2σ), and (v) the cemetery saw a very brief surge of burials potentially related to a catastrophic event. The results of this analysis thus shed light on the little-known chronological sequence of prehistoric hypogea or rock-cut tombs in Iberia, their spread, and their relation to other Late Neolithic collective burials in western Europe.
Keywords: Datación - Método del carbono 14 - La Beleña (Yacimiento, Córdoba); Estadística bayesiana; Bayesian modelin; Collective Burials; Late Neolithic; Iberian Peninsula; Hypogeum